The pedagogy of love and tenderness in the hospital classrooms of Peru - Mendoza Carrasco, Mariella Victoria (2019)
The approach of the Pedagogy of tenderness and love is called to analyze and take other paradigms; such as the study and development of social skills and interpersonal aspects; this pedagogy, mainly mentions, that tenderness should be considered as a virtue, as an essential factor in our educational, family and professional practice. The Pedagogy of Tenderness and the Pedagogy of the Hospital are closely linked and linked with the attention to the human being, in its most vulnerable stages. Thus, in Pedagogy Hospital is applied, Pedagogy of Tenderness as a didactic strategy, which helps the student - patient is more eager to learn and in turn improve their quality of life during the process and time of hospitalization.